2004
DOI: 10.1111/j.1600-0749.2004.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics Tools for the Analysis of Zebrafish Pigment

Abstract: Genetic model organisms are increasingly valuable in the postgenomics era to provide a basis for comparative analysis of the human genome. For higher order processes of vertebrate pigment cell biology and development, the mouse has historically been the model of choice. A complementary organism, the zebrafish (Danio rerio), shares many of the signaling and biological processes of vertebrates, e.g. neural crest development. The zebrafish has a number of characteristics that make it an especially valuable model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 103 publications
(165 reference statements)
0
37
0
Order By: Relevance
“…S5A and B; MO2). 7,19,20 We found that further knockdown of atp6v0ca by the MOs was more effective in suppressing the opaque yolk phenotype in cis-spns1 hi891/hi891 ;atp6v0ca cm/cm animals compare with the single spns1 hi891/hi891 mutant ( Fig. 7A and B, and Fig.…”
Section: Developmental Life-span Models For Regulation By the Balancementioning
confidence: 87%
See 3 more Smart Citations
“…S5A and B; MO2). 7,19,20 We found that further knockdown of atp6v0ca by the MOs was more effective in suppressing the opaque yolk phenotype in cis-spns1 hi891/hi891 ;atp6v0ca cm/cm animals compare with the single spns1 hi891/hi891 mutant ( Fig. 7A and B, and Fig.…”
Section: Developmental Life-span Models For Regulation By the Balancementioning
confidence: 87%
“…7 The phenotype induced by the atp6v0ca knockdown during early development was particularly evident based on hypopigmentation observed at 48 hpf., 7,19,20 By further performing atp6v0ca MO1 injections into spns1-mutant embryos we demonstrated an increased number of viable larvae with temporally ameliorated yolk phenotype through 120 hpf (Fig. 1D).…”
Section: Chemical and Genetic Modulations Of V-atpase In Spns1-deficimentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many prominent examples for this approach in model organisms such as bacteria, yeast, C. elegans, Drosophila, and zebrafish [21][22][23][24]. In contrast stands reverse genetics, in which one goes from a gene/sequence, often discovered via high-throughput Gene-phenotype correlation FIGURE 4.2 Schematic workflow of forward-and reverse genetic screens.…”
Section: Dissection Of Physiological and Pathological Processes With mentioning
confidence: 99%